Proposed strategy improvement for Citilink Airlines to increase market share - Darmawan, Adhytia Pradiktha; Wandebori, Harimukti (The Indonesian Journal of Business Administration, 2013)
Airline industry is one of the areas of business that affected by economic growth in Indonesia. According to Ministry of Transportation, the number of domestic and international passengers has increase from 2009 until now. Meanwhile, according to Minister of Tourism and Creative Economy, Indonesia is the third in the world in middle-class society people after China and India. This conditions stimulate grow in Low Cost Carrier (LCC) airlines industry. Citilink is a low-cost airline headquartered in Jakarta, Indonesia. It was established in 2001 as a low-cost subsidiary of Garuda Indonesia. The competition among LCC aviation is very competitive in Indonesia. Nowadays, features given by every LCC airlines is more sophisticated, this condition impact Citilink service to be more perfect both in tangible and intangible part for increasing customer satisfaction.The focus of this thesis is to find a solution that can help Citilink to increase the market share. Author gather a data based on interview with Citilink managements, collecting questionnaire about perception and expectation of Citilink by consumers, and analyzing business situation (external analysis and internal analysis).  The analysis shows that the root of the problem that caused the lost market share of Citilink Airline is the low level of customer satisfaction, human resources that existed at Citilink Airlines.To solve the business issue faced by Citilink, author proposes improvement strategy formulation based on the data gathered. Some service strategies recommendations are proposed to respond these conditions. The resulting strategy is to improve the quality of supporting crew as human resources and optimizing use of technology advance to increase efficiency in Citilink activity.